FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PEMBERIAN ASI EKSKLUSIF FACTORS RELATED TO EXCLUSIVE BREASTFEEDING - Winda Agustina (LPPM STIKES Siti Hajar dan Insight Power, 2022)
Based on WHO data, that only 44% of newborns in the world are breastfed within the first hour of birth. The results of the initial survey conducted to 10 mothers with babies aged 6 months over-12 months at the Sentosa Baru Health Center, showed that 7 mothers did not give exclusive breastfeeding, while 3 mothers gave exclusive breastfeeding. The purpose of this study was to determine the factors associated with exclusive breastfeeding. The study used an analytical survey method with a cross sectional approach. The study population was all mothers who had babies aged 6 months to 12 months as many as 44 people with a sample of 44 people who were taken using accidental sampling technique. Data analysis used univariate and bivariate analysis with chi-square test statistics. The results showed that the p value for the knowledge = 0.001, attitude = 0.001 and family support = 0.017, which means that knowledge, attitudes and family support have a relationship with exclusive breastfeeding. The conclusion of this study is that there is a relationship between knowledge, attitudes and family support with exclusive breastfeeding at the Sentosa Baru Health Center, Medan Perjuangan District, Medan City. It is suggested that this research can be used as material to increase knowledge and attitudes of breastfeeding mothers through counseling about the benefits and advantages of exclusive breastfeeding for infants and for mothers themselves.Keyword : Related Factors, Giving, Exclusive Breastfeeding